River avulsions on the Taquari megafan, Pantanal wetland, Brazil - Assine, M. L. (Elsevier B.V., 2005)
The Pantanal wetland is located in a tectonically active interior sedimentary basin in west-central Brazil. The south-flowing Paraguay River is the trunk-river of an alluvial constructional landform comprising several large alluvial fans, the largest one of which is the Taquari megafan. The Taquari River flows in two distinct geomorphologic zones within the megafan. Entrenched on sediments of Pleistocene fan lobes, the Taquari River flows in a 3 to 5 km wide meander belt in the upper fan, where avulsion is hindered by entrenchment. Downstream of the intersection point, stream discharge progressively decreases and the Taquari River becomes narrow and shallow toward the Paraguay River plain. Within the distributary fan lobe, the channel-levee sandy complex is topographically higher than the adjacent floodplains and avulsion is a natural consequence of crevasses in the natural levees. Many channel avulsions have occurred during the last decades and documented cases show that significant channel changes may take place in a few years. Beginning with crevassing in 1988 and ending with the abandonment of the former channel in 1998, the river completely changed course in the lower fan. Presently, a major avulsion is occurring in the upper portion of the growing fan lobe, where many crevasses have appeared in the natural levees with associated splays onto the floodbasin. New anastomosed channels have formed north of the Taquari River, but downstream of them the flow is unconfined and the water spreads into natural floodbasins. This avulsion is still in process and allows observation of channel evolution, the geomorphic features produced, the sedimentary processes involved, and resulting effects. If the new channels do not rejoin the main channel, the river mouth may abandon its present master channel and shift to a position a hundred kilometers north from its present position. A large volume of sediment has been transferred to the floodbasin, with progradation of crevasse splay deposits over fine overbank sediments. Many geomorphic features, recognizable in satellite and radar images, clearly show that avulsion has occurred many limes before in the Taquari River. Avulsion belt deposits and former diverted channels testify to ancient avulsion events within the fan lobe and show that progradation of splays onto the floodbasin is the most important infilling process within the Taquari distributary fan lobe. The avulsion process in the lower Taquari River has accelerated in the last 30 years, along with the magnitude of flooding. Pasture and intensive agriculture in the catchment area has increased the sediment supply to the wetland, but larger floods are also a consequence of higher rainfall since 1973. Avulsion and floods have been a cause of great concern among the local population and landowners. Before human intervention in attempting to control floods, however, a better understanding of the avulsive river system is needed, especially because a major navigation project including the channelization of the Paraguay River was recently proposed. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: avulsion; alluvial fan; Megafan; Taquari River; Pantanal wetland